2017
DOI: 10.5194/amt-10-3877-2017
|View full text |Cite
|
Sign up to set email alerts
|

Bias assessment of lower and middle tropospheric CO<sub>2</sub> concentrations of GOSAT/TANSO-FTS TIR version 1 product

Abstract: Abstract. CO 2 observations in the free troposphere can be useful for constraining CO 2 source and sink estimates at the surface since they represent CO 2 concentrations away from point source emissions. The thermal infrared (TIR) band of the Thermal and Near Infrared Sensor for Carbon Observation (TANSO) Fourier transform spectrometer (FTS) on board the Greenhouse Gases Observing Satellite (GOSAT) has been observing global CO 2 concentrations in the free troposphere for about 8 years and thus could provide a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…3 to improve the display of the quality of the figure to avoid a cluttered image and the omitted pressure levels don’t add value (not showing different distribution than the other used pressure levels). The results are different from those in other studies, almost all of which focus on regional characteristics 19 or individual heights 13 . A recent published paper developed a new monthly zonal mean carbon dioxide (CO 2 ) distribution from the upper troposphere to the stratosphere (5–42 km) over 2000–2010 based on a Lagrangian backward trajectory model driven by ERA-Interim reanalysis meteorology and tropospheric CO 2 measurements 29 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…3 to improve the display of the quality of the figure to avoid a cluttered image and the omitted pressure levels don’t add value (not showing different distribution than the other used pressure levels). The results are different from those in other studies, almost all of which focus on regional characteristics 19 or individual heights 13 . A recent published paper developed a new monthly zonal mean carbon dioxide (CO 2 ) distribution from the upper troposphere to the stratosphere (5–42 km) over 2000–2010 based on a Lagrangian backward trajectory model driven by ERA-Interim reanalysis meteorology and tropospheric CO 2 measurements 29 .…”
Section: Discussioncontrasting
confidence: 99%
“…In previous published work, the largest negative biases in the Thermal and Near Infrared Sensor for Carbon Observation-Fourier Transform Spectrometer (TANSO-FTS) TIR V1 CO 2 profile of GOSAT were found in the mid-troposphere region centred at 500–400 hPa 13 , and the monitoring accuracy of the GOSAT CO 2 concentrations has been determined experimentally to be 4 ppmv 37,38 , which is less sensitive to CO 2 in the mid-troposphere (500 hPa) 26 . The accuracy of AIRS is approximately 1–2 ppmv 36 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In summary, Saitoh et al (2016) found that the CO 2 profile data had consistent negative biases of 1.0%-1.5% as compared with the CME CO 2 data in the LT and MT regions (736-287 hPa). Saitoh et al (2017) found that the CO 2 profile data at the CME altitude range (approximately 11 km) was less than 0.5 ppmv at lower latitudes and 1.0 ppmv at middle and high latitudes. In addition, after applying the bias correction coefficient based on a comparison with CONTRAIL, both the trends and seasonal fluctuations showed good agreement with the Nonhydrostatic Icosahedral Atmospheric Model (NICAM)-Transport Model (TM) (Niwa et al, 2011(Niwa et al, , 2012 after inverse analysis.…”
Section: Gosat Observation Overview and Spectral Informationmentioning
confidence: 90%
“…While there are several other space-based instruments which obtain CO 2 absorption spectra in the thermal infrared region (TIR), such as Infrared Atmospheric Sounding Interferometer (IASI), we focus only on measurements from the SWIR and relevant instruments. SWIR measurements have sensitivity to the total CO 2 column down to the surface, whereas TIR measurement sensitivity is peaked at the middle and upper troposphere [3,4]. Both GOSAT and GOSAT-2 feature Fourier transform spectrometers (TANSO-FTS and TANSO-FTS-2) that point to specific locations for each single measurement.…”
Section: Introductionmentioning
confidence: 99%